2015
DOI: 10.1186/s12870-015-0501-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of variation in heading date among Asian rice accessions

Abstract: BackgroundHeading date, a crucial factor determining regional and seasonal adaptation in rice (Oryza sativa L.), has been a major selection target in breeding programs. Although considerable progress has been made in our understanding of the molecular regulation of heading date in rice during last two decades, the previously isolated genes and identified quantitative trait loci (QTLs) cannot fully explain the natural variation for heading date in diverse rice accessions.ResultsTo genetically dissect naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 69 publications
0
43
0
1
Order By: Relevance
“…CSSLs represent genetic resources that introgress a single (or a few) chromosomal segment(s) that collectively span the entire genome. Because the recent quantitative trait locus (QTL) analyses for flowering time derived from diverse Asian rice accessions have mapped the various QTLs influencing the genetic architecture of rice flowering time (Hori et al ., ), this compelled us to elucidate a wide range of naturally occurring variations of rice flowering‐time genes originated from diverse rice accessions in a common genetic background, and to simultaneously compare functional differences among various flowering‐time gene alleles using a large set of CSSL populations (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…CSSLs represent genetic resources that introgress a single (or a few) chromosomal segment(s) that collectively span the entire genome. Because the recent quantitative trait locus (QTL) analyses for flowering time derived from diverse Asian rice accessions have mapped the various QTLs influencing the genetic architecture of rice flowering time (Hori et al ., ), this compelled us to elucidate a wide range of naturally occurring variations of rice flowering‐time genes originated from diverse rice accessions in a common genetic background, and to simultaneously compare functional differences among various flowering‐time gene alleles using a large set of CSSL populations (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…To identify Tos17 insertion mutations of Hd1 , we selected mutant lines showing an early‐flowering phenotype in a paddy field of NIAS (Tsukuba, Japan; 36°03′N, 140°11′E) and then extracted genomic DNA from leaves of the mutant lines by the methods of Hori et al. (). We performed Southern blot analysis according to the method reported by Miyao et al.…”
Section: Methodsmentioning
confidence: 99%
“…, Hori et al. ). Sequence analysis of the known flowering‐time genes has indicated that allelic differences have contributed greatly to this phenotypic variation (Takahashi et al.…”
mentioning
confidence: 99%
“…Over-expression of Hd1 causes a delay in flowering under SD conditions and a single extension of day-length decreases Hd3a expression consistently with the duration of daylight [44,59]. The repression of flowering by Hd1 under LD conditions is enhanced by the kinase activity of Heading date 6 (Hd6), a gene encoding the α subunit of protein kinase CK2 (CK2α) [58]. Hd6 is a QTL involved in photoperiod response in rice.…”
Section: Circadian Clock and Photoperiod Responsementioning
confidence: 99%
“…The plant circadian system consists of biochemical timing mechanisms that temporarily modulate the function of several signalling pathways to measures changes in day-length and promote suitable timing of flowering to maximize reproductive success [2,3,6,7,9,10,[13][14][15]21,24,26,28,29,31,36,38,41,42,46,48,49,[56][57][58][59][60][61][62][63][64][65][66]. The photoperiod response on flowering time varies among grasses.…”
Section: Circadian Clock and Photoperiod Responsementioning
confidence: 99%